CUSTOMER RELATIONSHIP MANAGEMENT DESIGN IN OREGANO KITCHEN AND DESSERT BASED ON A RESPONSIVE WEB - Andrian Putra, Riko (Ikatan Dosen Menulis, 2025)
Customer Relationship Management (CRM) is a system developed with the aim of supporting companies in building close relationships with their customers. Because customers are a very important aspect for the company. (CRM) is also a widely implemented strategy for managing relationships between companies and customers and potential customers. Currently, Oregano Kitchen and Dessert is still experiencing difficulties in conveying information and food promotions to customers because the promotional media that is currently running is still not optimal and customers are still having difficulty ordering places and food. In this research the author used PHP and MySQL as well as UML in the software design process. Using a web-based Customer Relationship Management (CRM) system can make it easy for customers to order food and places and the company admin/owner can respond quickly to customer orders.